Quality control of effervescent vitamin C tablets sold in the city of Manaus - AM (Research, Society and Development, 2021)
Vitamin C effervescent tablets have been the most used pharmaceutical form in recent times due to its effervescent pharmaceutical form. In addition to the fact that studies show its properties in fighting free radicals as well as strengthening the immune system. With that in mind, this article aimed to analyze 5 effervescent vitamin C tablets, in order to verify if the same standards of quality standards required by Organs responsible bodies. The parameters followed standardized methodology by the substance monograph according to the Brazilian Pharmacopoeia, 6th edition, being physical-chemical determination of pH, friability, average weight and acidity content using the Balentine method by titration. Analyzes were performed in triplicate for greater confidence in the results. After analyzing the data, it was found that sample A did not meet the basic parameters recommended by law, failing the friability test. After the analyses, it was concluded that as they obtained satisfactory results, except for sample A, which failed the friability test, average weight and, most importantly, the dosage test, where it did not reach the 90% restore required by the monograph. The others meet the recommended criteria. Quality control jobs provide a very important tool in relation to the quality of products consumed, protecting the consumer and helping to improve the quality controls of products in the market.